2005
DOI: 10.1089/acm.2005.11.293
|View full text |Cite
|
Sign up to set email alerts
|

Engaging in the Audit of Acupuncture Practice

Abstract: Although willing to be involved, practitioners found the research process time-consuming and were concerned how it could be balanced against the demands of a busy practice and the interests of patients. For a national audit study to succeed, the process would have to be simplified and practitioners encouraged to engage; collection of such information could then help to provide much-needed data on acupuncture treatment in the United Kingdom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…e . a specific beneficial outcome, often in relation to a particular symptom or condition as the following examples highlight: “ long-term relief of symptoms” [ 46 ], “ help relieve pain better” [ 47 ], “ to increase energy” [ 48 ], “ improve their general health” [ 49 ], “ relief of my fibromyalgia ” [ 50 ], and “ about once a month I tell her I need a limberin’ up job” [ 51 ]. Others used CAM preventatively e .…”
Section: Resultsmentioning
confidence: 99%
“…e . a specific beneficial outcome, often in relation to a particular symptom or condition as the following examples highlight: “ long-term relief of symptoms” [ 46 ], “ help relieve pain better” [ 47 ], “ to increase energy” [ 48 ], “ improve their general health” [ 49 ], “ relief of my fibromyalgia ” [ 50 ], and “ about once a month I tell her I need a limberin’ up job” [ 51 ]. Others used CAM preventatively e .…”
Section: Resultsmentioning
confidence: 99%
“…Previous observation in the UK indicated that participation was facilitated if practitioners provided an initial commitment to learn about research (45). Certainly it has proved difficult to engage acupuncturists in research in the UK and probably other countries in the EU (Bovey et al, 2005;Fitter and Thomas, 2005). Lack of time when running a busy practice is usually cited as the main obstacle (Wayne et al, 2008).…”
Section: Researching Practicementioning
confidence: 99%
“…This represents a score that is clinically significant rather than statistically significant; with a reduced change above one representing a positive change seen as important to the patient receiving the treatment. MYMOP is an outcome measure that can be used to collect clinically significant scores from individuals seeking treatment (Bovery et al, 2005). This problem-specific questionnaire has been shown to be a reliable tool when used in acupuncture studies to measure the quality of changes considered important for the individuals receiving treatment (Hull, Page, Skinner, Linville, & Coeytaux, 2006;Paterson, 1996;Paterson & Britten, 2003;Paterson, Unwin, & Joire, 2010).…”
Section: Data Collection and Results For Mymopmentioning
confidence: 99%